Art for Art's sake? The impact of arts education - Winner, Ellen; Goldstein, Thalia R.; Vincent-Lancrin, Stéphan (Paris : OECD, 2013)
Arts education is often said to be a means of developing critical and creative thinking. Arts education has also been argued to enhance performance in non-arts academic subjects such as mathematics, science, reading and writing, and to strengthen students' academic motivation, self-confidence, and ability to communicate and co-operate effectively. Arts education thus seems to have a positive impact on the three subsets of skills that we define as "skills for innovation": subject-based skills, including in non-arts subjects; skills in thinking and creativity; and behavioural and social skills. This report examines the state of empirical knowledge about the impact of arts education on these kinds of outcomes. The kinds of arts education examined include arts classes in school (classes in music, visual arts, theatre, and dance), arts-integrated classes (where the arts are taught as a support for an academic subject), and arts study undertaken outside of school.
Executive summary -- The impact of arts education : from advocacy to evidence -- Cognitive outcomes of multi-arts education -- Cognitive outcomes of music education -- Cognitive outcomes of visual arts education -- Cognitive outcomes of theatre education -- Cognitive outcomes of dance education -- Creativity outcomes of arts education -- Motivational outcomes of arts education -- Social skills outcome of arts education -- Brain outcomes of arts education -- Why arts education? Summary and conclusions.
boek